Endogenous Antimicrobial Peptide Expression in Response to Bacterial Epidermal Colonization - Brandwein, Michael; Bentwich, Zvi; Steinberg, Doron (Frontiers in Immunology, 2017)
Bacterial commensal colonization of human skin is vital for the training and maintenance of the skin’s innate and adaptive immune functions. In addition to its physical barrier against pathogen colonization, the skin expresses a variety of antimicrobial peptides (AMPs) which are expressed constitutively and induced in response to pathogenic microbial stimuli. These AMPs are differentially effective against a suite of microbial skin colonizers, including both bacterial and fungal residents of the skin. We review the breadth of microorganism-induced cutaneous AMP expression studies and their complementary findings on the efficacy of skin AMPs against different bacterial and fungal species. We suggest further directions for skin AMP research based on emerging skin microbiome knowledge in an effort to advance our understanding of the nuanced host-microbe balance on human skin. Such advances should enable the scientific community to bridge the gap between descriptive disease-state AMP studies and experimental single-species in vitro studies, thereby enabling research endeavors that more closely mimic the natural skin environs.